2021
DOI: 10.1088/1361-6463/abd9a6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring plasma-generated ·OH and O atoms in liquid using EPR spectroscopy and the non-selectivity of the HTA assay

Abstract: Plasma-generated hydroxyl radicals (·OH) and oxygen atoms (O) produced by the COST reference plasma jet, a micro-scaled atmospheric pressure plasma jet, were investigated using a variety of experimental techniques. Several gas admixtures were studied to distinguish the contributions of the two reactive oxygen species. Large discrepancies between inferred aqueous ·OH densities were noted when using a 2-hydroxyterephthalic acid (HTA) fluorescence assay and electron paramagnetic resonance (EPR) measurements with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 68 publications
1
56
1
Order By: Relevance
“…[34] Here, the He/H 2 O admixture was selected based on the extensive characterization of the gas and liquid phase performed in previous experiments. [30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others.…”
Section: Plasma Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…[34] Here, the He/H 2 O admixture was selected based on the extensive characterization of the gas and liquid phase performed in previous experiments. [30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others.…”
Section: Plasma Setupmentioning
confidence: 99%
“…[30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others. The nozzle of the COST-Jet was placed 4 mm above the liquid surface, see Figure 1.…”
Section: Plasma Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…For the quantification of plasma-generated, short-lived ROS (hydroxyl radicals, atomic oxygen) solution of 5 mM terephthalic acid in 25 mM phosphate buffer, pH 7.4 was used despite the limited selectivity [59]. The reaction yield to the fluorescent compound 2-hydroxyterephthalic acid (HTPA) that could be quantified at 318 nm excitation and 426 nm emission using an external calibration curve.…”
Section: Oh and H 2 O 2 Quantification Via Colorimetric Assays In Liquidsmentioning
confidence: 99%